The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1002/psc.598
|View full text |Cite
|
Sign up to set email alerts
|

Structure‐activity relationship study of anoplin

Abstract: Anoplin is a decapeptide amide, GLLKRIKTLL-NH2 derived from the venom sac of the solitary spider wasp, Anoplius samariensis. It is active against Gram-positive and Gram-negative bacteria and is not hemolytic towards human erythrocytes. The present paper reports a structure-activity study of anoplin based on 37 analogues including an Ala-scan, C- and N-truncations, and single and multiple residue substitutions with various amino acids. The analogues were tested for antibacterial activity against both S. aureus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
62
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(65 citation statements)
references
References 45 publications
3
62
0
Order By: Relevance
“…Freshly drawn human erythrocytes in CPD (citrate-phosphatedextrose) buffer were obtained from the Copenhagen University Hospital blood bank (Copenhagen). Ifrah et al (2005). MALDI-TOF-MS was done on a VG Tof Spec E Fisons instrument (Fisons Instruments), using a-cyano-p-hydroxycinnamic acid as matrix.…”
Section: Chemicals and Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Freshly drawn human erythrocytes in CPD (citrate-phosphatedextrose) buffer were obtained from the Copenhagen University Hospital blood bank (Copenhagen). Ifrah et al (2005). MALDI-TOF-MS was done on a VG Tof Spec E Fisons instrument (Fisons Instruments), using a-cyano-p-hydroxycinnamic acid as matrix.…”
Section: Chemicals and Materialsmentioning
confidence: 99%
“…Protected amino acids were coupled in fourfold excess employing a protocol using HATU/DIEA (1:1.5) activation as described by Ryge et al (2004). Cleavage and deprotecting were carried out using reagent L: TFA/TIS/DTT/H 2 O (88:2:5:5) for 2 h. The final workup was performed as described by Ifrah et al (2005). The peptide products were purified by preparative HPLC and lyophilized, and the masses were verified by MALDI TOF-MS.…”
Section: Chemicals and Materialsmentioning
confidence: 99%
“…The peptide was discovered by Konno et al (12) and is a decapeptide amide found in the venom of the Japanese solitary spider wasp (Anoplius samariensis). Amino acid positions that are important for anoplin activity have been identified by a substitution and truncation study (13). This generally showed that replacement of a hydrophilic amino acid with a hydrophobic one increased both antimicrobial activity and hemolysis.…”
mentioning
confidence: 99%
“…Several laboratories have shown that disrupting the ␣-helix propensity by insertion of a central D-form amino acid decreases hemolytic activity more than it decreases antimicrobial potency (15)(16)(17)(18)(19)(20)(21)(22). Other approaches include modification of the termini (23,24), modification of the charge and hydrophobicity (13,14,(25)(26)(27), retro and inverso synthesis (24), as well as cyclization (28).…”
mentioning
confidence: 99%
See 1 more Smart Citation